2010
DOI: 10.1021/ja104373e
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Building Blocks of Self-Assembled Peptide Nanotubes

Abstract: In the world of biology, "self-assembly" is the ability of biological entities to interact with one another to form supramolecular structures. One basic group of self-assembled structures is peptide nanotubes (PNTs). However, the self-assembly mechanism, with its special characteristics, is not yet fully understood. An exceptional quantum-confined approach is shown here for the self-assembly mechanism in bio-inspired materials. We found the elementary building block of the studied PNT, which is self-assembled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 32 publications
8
151
0
2
Order By: Relevance
“…The UniProtKB/Swiss-Prot database indicates that P450s are rich in aromatic amino acids: 90% of the sequences in the P450 family (956 sequences) have above-average occurrence of Phe residues; and 68% of the sequences have more Trp residues than average. Phe residues are unlikely to participate as real intermediates in ET reactions, but their role in enhanced superexchange coupling for long-range ET remains unresolved [46][47][48]. Cytochrome P450 BM3 (CYP102A1) is frequently used as a soluble surrogate for human microsomal P450 s [44].…”
Section: Protecting P450s?mentioning
confidence: 99%
“…The UniProtKB/Swiss-Prot database indicates that P450s are rich in aromatic amino acids: 90% of the sequences in the P450 family (956 sequences) have above-average occurrence of Phe residues; and 68% of the sequences have more Trp residues than average. Phe residues are unlikely to participate as real intermediates in ET reactions, but their role in enhanced superexchange coupling for long-range ET remains unresolved [46][47][48]. Cytochrome P450 BM3 (CYP102A1) is frequently used as a soluble surrogate for human microsomal P450 s [44].…”
Section: Protecting P450s?mentioning
confidence: 99%
“…These d-spacings are consistent with the crystalline structure of the FF tube formation 26 and coincide with XRD of the PND (this latter XRD were obtained by powder-XRD of PNDs aggregates and not from single PND as in here). 12 The lateral size distribution of the FF PND that was estimated from the TEM images is 2.4 ± 0.6 nm (Fig. 1(c)).…”
Section: -25mentioning
confidence: 95%
“…Recently we have found that in anhydrous conditions the tubes can disassemble into stable building blocks of peptide nanodots (PNDs). 12 Thus, the nm-scaled (∼2 nm in diameter) PND architecture opens new opportunities for the integration of FF-based structures in bio-electronics devices.…”
Section: © 2013 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nanotechnology research revealed that peptides can self-assemble into peptide nanotubes by a mechanism that is not yet understood fully. These peptide nanotubes can be components of metallic/semiconductor-organic frameworks (BioMOFs) ( Figure 6C) (Amdursky et al, 2010). Consequently, we may assume that peptides can form biosemiconductors in vivo too.…”
Section: Biosemiconductorsmentioning
confidence: 99%